436 Examining the Role of Obesity and Leptin Signaling in Triple Negative Breast Cancer. (April 2022) - Brock, Courtney; Wright, Maryl K.; Nguyen, Khoa; Hebert, Katherine; Alzoubi, Madlin; Cheng, Thomas; Collins-Burow, Bridgette M.; Burow, Matthew E.
Abstract : OBJECTIVES/GOALS: In triple negative breast cancer (TNBC), obesity is associated with poor outcomes. Adipose stem cells (ASCs) from obese patients (obASCs) secrete higher levels of adipokines compared to ASCs from lean individuals. Leptin, one of these adipokines, has been implicated in many cancers. This study seeks to examine the role of leptin signaling in TNBC. METHODS/STUDY POPULATION: Previous work in conjunction with a collaborating lab has shown that leptin signaling promotes metastasis and increased expression of epithelial-mesenchymal transition (EMT) markers in triple negative breast cancer cell lines. This project expands upon this work through using both patient-derived cell lines and and patient-derived xenografts (PDX), and examines the role of leptin signaling both in vitro and in vivo. To determine the effects of obesity upon a PDX model of TNBC, a high fat diet was used to induce obesity in vivo. A pharmacological inhibitor of the leptin receptor was used to test the requirement for leptin signaling both in vivo and in vitro. RESULTS/ANTICIPATED RESULTS: Exposure to conditioned media harvested from obASCs increased the percentage of TNBC cells that expressed cancer stem cell markers, whereas exposure to an inhibitor of the leptin receptor decreased the percentage of cells with cancer stem cell markers. PDX tumors implanted into mice with diet-induced obesity had an increased volume compared to tumors implanted into lean controls. Further analysis will be conducted on metastasis, circulating tumor cells, and survival in both lean and obese mice. DISCUSSION/SIGNIFICANCE: Understanding the complex signaling events in the obese tumor microenvironment is essential, as these molecular differences may contribute to different outcomes for obese and lean individuals with triple negative breast cancer. Therefore, study of the crosstalk between obASCs and TNBC cells is critical.